Novel Lessons on Behavioral Ethics From the U.S. Military Academy at West Point. (August 2017) - Offstein, Evan H.; Dufresne, Ronald L.; Childers, J. Stephen
After a spate of business ethics crises over the past two decades, management educators were put on notice: considerably more was needed to improve the ethical grounding of our graduating students. Taking stock of our progress, we contend that management education remains well short of achieving this charge and cannot be content with the state of its ethics development. In this essay, grounded on a 2-year research platform, we turn to a unique institute of higher education to comment on the pedagogical assumptions and practices they enact to enhance the ethical behavior of their students. Specifically, this essay will comment on some of the more novel and paradoxical principles and approaches employed by the U.S. Military Academy at West Point to support the positive ethical behaviors of its students. We offer meaningful prescriptions touching on core planks of behavioral ethics: moral awareness, moral decision making, and moral motivation. Given the questionable efficacy of some previous approaches at improving ethical behavior, turning our attention to this unique institution may offer some compelling insights that may be employed in management education.